2019
DOI: 10.1038/s41467-018-08042-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechano-chemical decomposition of organic friction modifiers with multiple reactive centres induces superlubricity of ta-C

Abstract: Superlubricity of tetrahedral amorphous carbon (ta-C) coatings under boundary lubrication with organic friction modifiers is important for industrial applications, but the underlying mechanisms remain elusive. Here, combined experiments and simulations unveil a universal tribochemical mechanism leading to superlubricity of ta-C/ta-C tribopairs. Pin-on-disc sliding experiments show that ultra- and superlow friction with negligible wear can be achieved by lubrication with unsaturated fatty acids or glycerol, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
123
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 46 publications
(66 reference statements)
12
123
0
Order By: Relevance
“…The DLC surface underwent permanent deformation at the nanoscale when subjected to forces as small as tens of nano-Newtons. Recently, Kuwahara et al [22] using sliding experiments of ta-C/ta-C tribopairs showed that superlubricity with negligible wear can be achieved by lubrication with unsaturated fatty acids or glycerol. Zhang et al [23] using high-intensity pulsed ion beam irradiated WC-Ni surface against graphite under water lubrication also got significant friction reduction.…”
Section: Solid Superlubricity 2211 Superlubricity Of Diamond-like mentioning
confidence: 99%
“…The DLC surface underwent permanent deformation at the nanoscale when subjected to forces as small as tens of nano-Newtons. Recently, Kuwahara et al [22] using sliding experiments of ta-C/ta-C tribopairs showed that superlubricity with negligible wear can be achieved by lubrication with unsaturated fatty acids or glycerol. Zhang et al [23] using high-intensity pulsed ion beam irradiated WC-Ni surface against graphite under water lubrication also got significant friction reduction.…”
Section: Solid Superlubricity 2211 Superlubricity Of Diamond-like mentioning
confidence: 99%
“…Notably, ultralow friction can be achieved also in the absence of such lubricants. Thus, amorphous carbon coatings can provide ultralow friction coefficients [10][11][12][13] , and they are already used in industrial applications, including razor blades, magnetic hard drives, microelectromechanical systems and more.…”
Section: Openmentioning
confidence: 99%
“…This is a good indication that C 4 H 10 and C 16 H 34 will undergo a very similar radicalization process when sheared under high pressure between diamond/W/WO 3 sliding interfaces. Additionally, in a different study (Kuwahara et al, 2019), short C 7 H 12 O 2 and long C 18 H 34 O 2 acid molecules, which have different molecular lengths but the same reactive centers, were investigated using tight binding, which is computationally less expensive than DFT. In that study, it was shown that short cis-heptanoic acid (C 7 H 12 O 2 ) molecules undergo very similar tribochemical reactions as the longer oleic acid (C 18 H 34 O 2 ) molecules during shearing under high pressure between sliding ta-C counter surfaces.…”
Section: Diamond the Aes Analysis Maps Inmentioning
confidence: 99%